2011
DOI: 10.1111/j.1365-313x.2011.04774.x
|View full text |Cite
|
Sign up to set email alerts
|

Cucumber mosaic virus suppressor 2b binds to AGO4‐related small RNAs and impairs AGO4 activities

Abstract: SUMMARYCucumber mosaic virus suppressor 2b (CMV2b) is a nuclear viral suppressor that interferes with local and systemic silencing and inhibits AGO1 slicer activity. CMV2b-mediated transgene hypomethylation and its localization in Cajal bodies suggests a role of CMV2b in RNA-directed DNA methylation (RdDM). However, its direct involvement in RdDM, or its binding with small RNAs (sRNAs) in vivo is not yet established. Here, we show that CMV2b binds both microRNAs (miRNAs) and small interfering RNAs (siRNAs) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
131
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(157 citation statements)
references
References 40 publications
14
131
0
12
Order By: Relevance
“…A recent finding suggested that this suppressor protein is indirectly involved in aphid transmission [56]. A study on mechanism of 2b action showed that the suppressor specifically recruits AGO4 small RNAs and directly interacts with PIWI and PAZ domains of AGO4 affecting its slicer activity, causing hypomethylation of its loci [18]. RNA3 encodes for two proteins: movement protein (MP) located at 5 0 end and coat protein which is expressed from another ORF through subgenomic RNA 4.…”
Section: Introductionmentioning
confidence: 99%
“…A recent finding suggested that this suppressor protein is indirectly involved in aphid transmission [56]. A study on mechanism of 2b action showed that the suppressor specifically recruits AGO4 small RNAs and directly interacts with PIWI and PAZ domains of AGO4 affecting its slicer activity, causing hypomethylation of its loci [18]. RNA3 encodes for two proteins: movement protein (MP) located at 5 0 end and coat protein which is expressed from another ORF through subgenomic RNA 4.…”
Section: Introductionmentioning
confidence: 99%
“…DCL3 has only a minor role against RNA viruses (Qu et al 2008;Raja et al 2014). The fact that silencing suppressors of RNA viruses interfere with DCL3 pathway suggests that DCL3 contributes to antiviral silencing (Azevedo et al 2010;Hamera et al 2012;Lacombe et al 2010). During antiviral silencing against DNA viruses DCL3 is essential and works presumably by inducing chromatin modifications (Akbergenov et al 2006;Blevins et al 2006;Raja et al 2014).…”
Section: Biogenesis Of Vsirnasmentioning
confidence: 99%
“…CMV 2b silencing suppressor protein directly interacts with AGO4 and inhibits its slicer activity and methylation and thus creates a favorable niche for CMV proliferation (Hamera et al 2012). AGO5 (besides AGO2) was shown to be required to inhibit PVX systemic infection .…”
Section: Effector Step Of Antiviral Silencingmentioning
confidence: 99%
See 2 more Smart Citations